The impact of information technology alignment on Zayed University performance: The moderation role of information technology flexibility - Alobthani, Manal Mane Salmeen (2024)
In certain emerging economies, higher education institutions (HEIs) struggle to effectively utilize the advantages of Information Technology (IT), resulting in stagnation in their operations. The problem this research addresses is the underutilization of IT and its alignment components within HEIs in the context of the United Arab Emirates (UAE). The overarching aim of this study is to investigate the impact of IT alignment factors on the institutional performance of HEIs, and to scrutinize the moderating role of IT flexibility in the relationships between IT components (including IT communications, IT competence/value measurement, IT governance/structure, IT partnerships, IT scope and architecture, and IT skills) and institutional performance. Data was collected from a sample of 310 employees at Zayed University employing a cross-sectional survey design. The instrument utilized was a questionnaire, and the analysis was performed using a Partial Least Squares approach within a Structural Equation Modelling framework. The findings of this study revealed that IT alignment significantly and positively impacts the performance of HEIs, with IT skills demonstrating the most potent effect. Additionally, IT flexibility was found to play a significant moderating role in the relationships between IT alignment components and the institutional performance of HEIs. Grounded in the Dynamic Capabilities Perspective Theory and Resource-Based Theory, this research contributes to the existing literature by highlighting the integral role of IT alignment in improving institutional performance. Furthermore, it underscores the importance of IT competency among senior management in influencing performance through effective IT alignment. This real world exploration of the complementarity between IT governance and IT competence extends the understanding of IT governance practices. The findings have practical implications for policymakers and HEIs' management, highlighting the potential benefits of investing in IT alignment and enhancing IT flexibility to boost institutional performance.